Sikap Demokratik dalam Pembelajaran Pendidikan Kewarganegaraan - Lubis, Syakwan (Jurnal Demokrasi, 2008)
Democratic attitude is very urgent to develop in learning process. This attitude required the involvement of teachers and students in planning, organizing, implementing, and controlling the learning process. This article tries to show how the democratic attitude can give a positive impact for students in developing their achievement and creativity in the learning process. Teachers should have this attitude in order that they can develop learning process to be more effective and meaningful. Kata kunci: Sikap demokratik, pembelajaran, hasil belajar, manajemen pembelajaran, kreatifitas